Computational engineering to enhance the photovoltaic by end‐capped and bridging core alterations: Empowering the future with solar energy through synergistic effect in D‐A materials. Issue 1 (12th September 2021) - Janjua, Muhammad Ramzan Saeed Ashraf; Haroon, Muhammad; Hussain, Riaz; Usman, Muhammad; Khan, Muhammad Usman; Gill, Waqas Amber
Abstract: Organic photovoltaic solar cells are being designed to offer a low energy photovoltaic (PV) solution. Optimizing the molecular backbone is one the most important technique for improving the photovoltaic characteristic of A‐D‐A type small active layer molecules. Herein, we have designed and theoretical characterized six new molecules by end‐capped and bridging core modifications of recently synthesized molecule BFHIC‐4F. Enhancement in photovoltaic, optoelectronic and physio‐chemical properties of newly designed molecules are seen by doing such modifications. Different advanced quantum chemical techniques have been employed to evaluate the performance of newly planned molecules. Large open circuit voltage and narrow band gap suggested that the designed molecules are efficient aspirants for solar cell applications. Moreover, maximum absorption capability in near‐infra‐red (NIR) region is observed for these newly designed molecules. To sum up, outcomes of all analyses advocated that the designed molecules are efficient candidates for solar cell applications. Abstract : Herein, we have designed and theoretical characterized six new molecules by end‐capped and bridging core modifications of recently synthesized molecule BFHIC‐4F. Enhancement in photovoltaic, optoelectronic and physio‐chemical properties of newly designed molecules are seen by doing such modifications. To sum up, outcomes of all analyses advocated that the designed molecules are efficient candidates for solar cell applications.